A Call For Improving Winter Windbreak Design for Lowbush Blueberry Production in the Saguenay–Lac-Saint-Jean Region of Québec, Canada. Issue 2 (3rd April 2019) - Girona, Jessica; Bradley, Robert; Lévesque, Josée-Anne; Paré, Maxime; Bellemare, Mireille
ABSTRACT: Wind exposure may reduce the snowpack and increase frost damage to lowbush blueberry ( Vaccinium angustifolium Ait.). Farmers in the Saguenay-Lac-Saint-Jean region (Québec) have therefore installed natural windbreaks to maintain a deep snow cover. We verified the efficiency of 39 windbreaks distributed over two farms. Over two consecutive years, snow depth was measured along transects established perpendicular to these windbreaks. In the first summer, frost damage and yields were assessed at each point where snow depth had been measured. We found large fluctuations in snow depth along most transects, with deeper snow occurring within 20 m on either side of windbreaks. Relative snow depth distribution was correlated between years on 19 transects. On one farm, one third of total transect length was below the recognized critical depth of 30 cm. On this farm, the proportion of damaged stems, the mean length of stem damage and the damaged-to-total stem length decreased exponentially with increasing snow depth. Likewise, the number of fruits per stem decreased exponentially with the length of stem damage and increased linearly with snow depth. Given current trends in climate change, our results serve as a timely call for improving winter windbreak design in the Saguenay-Lac-Saint-Jean region.